THE RELATIONSHIP BETWEEN EXCESSIVE SUGAR AND FAT INTAKE AND GESTATIONAL DIABETES MELLITUS - Umedova M. E.; Gulmirzayeva M. M. (The Conference Hub, 2025)
Gestational diabetes mellitus (GDM) is a condition characterized by hyperglycemia first diagnosed during pregnancy, which increases the risk of both short- and long-term complications for the mother and child. In recent years, the prevalence of GDM and pregnancy-related hyperglycemia has been increasing worldwide. According to the International Diabetes Federation (IDF) 2024 report, approximately one in six live births (≈15–16%) is affected by some form of hyperglycemia during pregnancy, with the majority of these cases attributable to GDM.